The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/ja077821p
|View full text |Cite
|
Sign up to set email alerts
|

Rhodostreptomycins, Antibiotics Biosynthesized Following Horizontal Gene Transfer from Streptomyces padanus to Rhodococcus fascians

Abstract: Two antibiotics have been isolated from a strain of Rhodococcus fascians that emerged from a competitive co-culture with Streptomyces padanus. The structures of these compounds were elucidated by detailed analyses by NMR and MS. They belong to the aminoglycoside family of antibiotics, and they are structurally unrelated to the actinomycins that are produced by S. padanus. The compounds have been named rhodostreptomycins A and B, reflecting their rhodococcal origin and streptomycin-like composition. Rhodostrept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 10 publications
0
48
0
3
Order By: Relevance
“…The horizontal exchange of genes in these pathways is well documented (18,21,23,26) and provides a rapid mechanism for bacteria to test the selective advantage afforded by the small molecule product(s) of complex biosynthetic pathways (12,23). Documenting the distributions of specific biosynthetic pathways among bacteria has the potential to add new insight into the extent to which these pathways are exchanged and how gene clusters evolve to create new chemical diversity.…”
mentioning
confidence: 99%
“…The horizontal exchange of genes in these pathways is well documented (18,21,23,26) and provides a rapid mechanism for bacteria to test the selective advantage afforded by the small molecule product(s) of complex biosynthetic pathways (12,23). Documenting the distributions of specific biosynthetic pathways among bacteria has the potential to add new insight into the extent to which these pathways are exchanged and how gene clusters evolve to create new chemical diversity.…”
mentioning
confidence: 99%
“…Recently, a new methodology was intruduced via coculture between a strain of Rhodococcus fascians that does not produce an antibiotic and a strain of S. padanus that is a highly stable actinomycin producer [7]. The Rhodococcus strain 307CO isolated from one such coculture produced novel antibiotics (rhodostreptomycin A and rhodostreptomycin B), which are isomers different from the configuration of the carbon atom at C6 in streptose [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new methodology was intruduced via coculture between a strain of Rhodococcus fascians that does not produce an antibiotic and a strain of S. padanus that is a highly stable actinomycin producer [7]. The Rhodococcus strain 307CO isolated from one such coculture produced novel antibiotics (rhodostreptomycin A and rhodostreptomycin B), which are isomers different from the configuration of the carbon atom at C6 in streptose [7]. Genetic analysis showed that a strain of Rhodococcus strain 307CO contained a large segment DNA derived from the Streptomyces strains, and there is correlation between antibiotic production and the presence of the Streptomyces DNA in the Rhodococcus [7].…”
Section: Introductionmentioning
confidence: 99%
“…Em estudos prévios, a utilização de culturas mistas estimulou a produção de metabólitos secundários e/ou aumentou a atividade biológica de extratos microbianos (WHITT et al, 2014;CHAGAS;DIAS;PUPO, 2013, RATEB et al, 2013ONAKA et al, 2011;NEWMAN, 2011;GLAUSER et al, 2009;PARK et al, 2009;PETTIT, 2009;KUROSAWA et al, 2008;ZHU et al, 2007;ANGELL et al, 2006;LIN, 2006;OH et al, 2005;DEGENKOLB et al, 2002;CUETO et al, 2001;SLATTERY;RAJBHANDARI;WESSON, 2001 A biossíntese do antibiótico pestalona (Figura 3) pelo fungo Pestalotia sp., é um exemplo de indução da expressão de uma rota biossintética em resposta a co-cultura com bactéria marinha unicelular (CUETO et al, 2001). Os diterpenos libertelenona A-D (Figura 3) também foram produzidos em resposta às interações microbianas na co-cultura entre o fungo Libertella sp.…”
Section: Interações Microbianas E Culturas Mistasunclassified